2019
DOI: 10.1039/c8bm01001c
|View full text |Cite|
|
Sign up to set email alerts
|

A testis-derived macroporous 3D scaffold as a platform for the generation of mouse testicular organoids

Abstract: Extracellular matrix-derived scaffolds provide an efficient platform for the generation of organ-like structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…We observed that the percentage of swelling slowly increased with the increase of the incubation time. Two groups of SDS 0.5, 30 and ST 0.5 for 30 min showed the maximum absorption of water after 72 h, about 60%, which is consistent with the similar investigations elsewhere [47]. Pore size is critical Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that the percentage of swelling slowly increased with the increase of the incubation time. Two groups of SDS 0.5, 30 and ST 0.5 for 30 min showed the maximum absorption of water after 72 h, about 60%, which is consistent with the similar investigations elsewhere [47]. Pore size is critical Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the percentage of scaffolds degradation slowly increased with increasing the incubation time, the weight of the scaffold remained intact, nearly 80 percent, following 30 days incubation. SDS 0.5, 30, and ST 0.5 for 30 min showed the maximum degradation rate because of having the highest hydrophilicity [47]. The swelling behavior of scaffolds facilitates cell migration, proliferation, and oxygen absorption and waste disposal [48].…”
Section: Discussionmentioning
confidence: 98%
“…These structures showed the development of a functional testicular blood barrier between the Sertoli cells without differentiation of the spermatogonial cells [105]. An additional study showed the development of mouse spermatogonial cells to meiotic and post meiotic cells in organoids when cultured in fabricated testis-derived scaffolds [106].…”
Section: Testicular Organoidsmentioning
confidence: 98%
“…7 Paclitaxel and docetaxel are two classical microtubule inhibitors that exert their activity by promoting tubulin polymerization and stabilization of microtubules, which results in G2-M phase arrest and mitotic cell death. 8,9 They have been widely adopted in treating breast cancer and pancreatic cancer patients. Despite being quite effective, severe hypersensitivity and other potentially dramatic side effects can be caused by paclitaxel and docetaxel.…”
Section: Introductionmentioning
confidence: 99%